"Im nationalen Abwehrkampf der Grenzlanddeutschen" Akademische Burschenschaften und Politik in Österreich nach 1945 - Weidinger, Bernhard (2014)
The book depicts the ideological foundations and political practice of pan-German student fraternities (Burschenschaften) in Austria after 1945. The Burschenschaften's post-war volkish (German) nationalism and interwovenness with the Austrian Freedom Party (FPÖ) receive particular attention.